Severe multiorgan failure following yellow fever vaccination - Domingo, Cristina; Lamerz, Judith; Cadar, Daniel; Stojković, Marija; Eisermann, Philip; Merle, Uta; Nitsche, Andreas; Schnitzler, Paul (Vaccines, 2020)
Background: The yellow fever (YF) vaccination is recommended by the WHO for people traveling or living in endemic areas at risk for yellow fever infections in Africa and South America. Although the live attenuated yellow fever vaccine is a safe and efficient vaccine, rare serious adverse events after vaccination have been reported. Case presentation: We present the case of a 74-year-old male with multiorgan failure after yellow fever vaccination for a trip to Brazil. The patient required admission to the intensive care unit with a prolonged stay due to severe organ dysfunction. Five days after the YF vaccination, the patient experienced nausea, vomiting, diarrhea, and general illness. Three days later he sought medical attention and was transferred to the University Hospital Heidelberg with beginning multiorgan failure and severe septic shock, including hypotonia, tachypnea, thrombopenia, and acute renal failure the same day. Within one week after vaccination, antibodies against YF virus were already detectable and progressively increased over the next two weeks. Viral RNA was detected in serum on the day of admission, with a viral load of 1.0 × 105 copies/mL. The YF virus (YFV) RNA was also present in tracheal secretions for several weeks and could be detected in urine samples up to 20 weeks after vaccination, with a peak viral load of 1.3 × 106 copies/mL. After 20 weeks in the ICU with nine weeks of mechanical ventilation, the patient was transferred to another hospital for further recovery. Conclusions: The risk for severe adverse events due to the YF vaccination should be balanced against the risk of acquiring a severe YF infection, especially in elderly travelers.
Gesehen am 27.08.2020